High Return Performance of Calcium Phosphonate (Ca-DTPMP) Colloidal Inhibitors for Squeeze Treatment in Shale Formations - Gao, Shujun; Dai, Chong; Wang, Xin; Zhao, Yue; Lu, Yi-Tsung; Deng, Guannan; Ko, Saebom; Paudyal, Samiridhdi; Harouaka, Khadouja; Kan, Amy T.; Tomson, Mason (Frontiers in Materials, 2020)
The objective of this work was to develop nanomaterial inhibitor with long squeeze life for oil and gas production. Different surfactants, trisodium citrate (Na3Cit), cetyltrimethyl ammonium bromide (CTAB), benzethonium chloride (Hyamine), and bipyridinium dibromide (Gemini), were added to synthesize nanoparticle Ca-DTPMP inhibitor at pH 9.0. The inhibitors were characterized by scanning electron microscope (SEM) and dynamic light scattering (DLS). All these surfactants significantly decreased the particle size, but Gemini was the most effective one to control the calcium phosphonate salt particle size to be about 500 nm. Long-term squeeze experiments (~ 3,000 PV) saturated with calcite at 70 oC and 75 psi back pressure through a glass column packed with Fayetteville shale rock show that the return DTPMP concentration was as high as 3 ppm for the Gemini-Ca-DTPMP colloidal inhibitor. This is an unprecedented improvement in comparison to the squeeze return of DTPMP only inhibitor where the inhibitor return concentration dropped to below 1 ppm within 400 pore volumes. The Ca-DTPMP speciation, potential field application, and the SqueezeSoftPitzer model prediction, are also discussed.